2013
DOI: 10.1111/nph.12352
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the proteome of Emiliania huxleyi CCMP 1516 to extremes of light is highly targeted

Abstract: SummaryOptimality principles are often applied in theoretical studies of microalgal ecophysiology to predict changes in allocation of resources to different metabolic pathways, and optimal acclimation is likely to involve changes in the proteome, which typically accounts for > 50% of cellular nitrogen (N).We tested the hypothesis that acclimation of the microalga Emiliania huxleyi CCMP 1516 to suboptimal vs supraoptimal light involves large changes in the proteome as cells rebalance the capacities to absorb li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 96 publications
4
63
0
Order By: Relevance
“…The number of RCII per cell is typically quantified by measuring the abundances of PSII and PSII reaction centre proteins using either biophysical techniques (Falkowski et al ., ) or Western blotting (Six et al ., ), whereas photosynthetic unit size is typically quantified by the ratio Chl a :RCII. In E. huxleyi the proportion of the proteome attributable to PSII was greater in LL than HL (McKew et al ., ), and the ratio Lhcf:PSII was also significantly greater in LL compared to HL (Fig. ), consistent with previous observations that photoacclimation in this species involves changes of both photosynthetic unit size and number (Suggett et al ., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The number of RCII per cell is typically quantified by measuring the abundances of PSII and PSII reaction centre proteins using either biophysical techniques (Falkowski et al ., ) or Western blotting (Six et al ., ), whereas photosynthetic unit size is typically quantified by the ratio Chl a :RCII. In E. huxleyi the proportion of the proteome attributable to PSII was greater in LL than HL (McKew et al ., ), and the ratio Lhcf:PSII was also significantly greater in LL compared to HL (Fig. ), consistent with previous observations that photoacclimation in this species involves changes of both photosynthetic unit size and number (Suggett et al ., ).…”
Section: Discussionsupporting
confidence: 92%
“…Our recent findings (McKew et al ., ) indicated that the photosynthetic proteins accounted for a greater proportion of the total proteome in LL, and in addition that the relative abundances of specific photosynthetic proteins also changed significantly between HL and LL. We reanalysed these data by first normalizing to the abundance of PSII core complex proteins (sum of spectral counts for detected proteins PsbA, B, C, D, E, H and V) as an internal photosynthetic unit reference before taking the ratio of these PSII‐normalized relative abundances between LL and HL (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…E. huxleyi is well known for its tolerance to high light and has been shown to resist photoinhibition at light intensities up to 1500 µmol photons m −2 s −1 (Nanninga & Tyrrell 1996). Surprisingly, a recent proteomic study found that such adaptation to high light did not involve enhanced production of FtsH or HCF136 (McKew et al 2013b), even though net D1 repair rates increased in cultures exposed to high photon flux densities (McKew et al 2013a). While these data suggest that other factors may be important to determine the rate of D1 repair in E. huxleyi, they also underscore the importance of FtsH and HCF136 in maintaining PSII integrity and function under a variety of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…imicrobe.us/project/view/104). In addition, a recent E. huxleyi proteomic study only detected SOD2A (364889) out of the 4 annotated isoforms (McKew et al 2013b), suggesting that MnSOD…”
Section: Selection Of Genes Involved In Psii Repair and Antioxidant Fmentioning
confidence: 99%
“…Species-specific transcriptomics, proteomics and metabolomics studies with marine microbes provided first insights into the significance of single genes or gene clusters for acclimation and adaptation of marine microbes to environmental conditions (e.g. Mock et al, 2008;Allen et al, 2008;Wecker et al, 2009;Zinser et al, 2009, Ashworth et al, 2013, McKew et al, 2013. Furthermore, those studies laid the foundation for biomarker discoveries to study natural communities.…”
Section: The Genetic Basis Of Adaptation and Metabolismmentioning
confidence: 99%